The virtual Marshall McLuhan - Theall, Donald F., 1928- (McGill-Queen's University Press, 2001)
"Marshall McLuhan explored everything from popular culture to the occult to the emerging digital revolution. In the Virtual Marshall McLuhan Donald Theall discusses the influences that shaped McLuhan's ideas and examines McLuhan's roles as artist, pop guru, shaman, and scholar. Theall, McLuhan's first doctoral student, provides new information about their relationship creating a picture of McLuhan as a complex human being, at one attractive, witty, egotistic, and exasperating."--Jacket